ANALYSIS OF THE ANAMNESIS, THE COURSE OF PREGNANCY AND CHILDBIRTH, THE MORPHOLOGICAL FEATURES OF THE PLACENTA IN WOMEN WITH PREMATURE BIRTH AND A FETUS WITH EXTREMELY LOW BODY WEIGHT - Елена Николаевна Кравченко; Ирина Вячеславовна Савельева; Галина Владимировна Кривчик; Лариса Владимировна Куклина; Евгения Сергеевна Казанцева (The Publishing House Medicine and Enlightenment, 2023)
Preterm birth (PR) with extremely low body weight is not only a medical problem, but also a social one. The aim of the research - to analyze the features of the anamnesis, the course of pregnancy and the morphological features of the placenta during childbirth with a fetus with an extremely low body weight. Materials and methods. The medical records of pregnancy and childbirth management of 47 patients who were observed in antenatal clinics in Omsk and gave birth to fetuses with extremely low body weight (ELBW) in the City Clinical Perinatal Center in 2022 were analyzed. Results. 25 women (53,2 %) had a complicated obstetric history, more often associated with several adverse events. Complications of gynecological anamnesis were observed in 26 (55,3 %) women. 33 patients (70,2 %) had endocrine pathology, the most significant for carrying a pregnancy. Every fourth patient (12 - 25,5 %) had gestational diabetes mellitus, every third (16 women - 34 %) had obesity, every sixth (7 - 14,9 %) had thyroid pathology. Pregravid preparation was carried out only in 6 (12,8 %) patients. Microscopic signs were expressed by acute chorioamnionitis and other manifestations of intrauterine infection. Various disorders of villi differentiation were determined, manifested by their delayed or accelerated maturation, signs of maternal and fetal malperfusion. Conclusion. The infectious factor is the leading factor in the development of PR with ELBW, so the main measures are a thorough history taking, identification of vaginal infections and sexually transmitted infections, asymptomatic bacteriuria, cervicometry. A rational approach to the management of pregnant women will eliminate the influence of manageable risk factors at the stage of preconception preparation and during pregnancy, implement timely diagnostic and therapeutic measures, and minimize adverse obstetric and perinatal outcomes.